TIPOLOGI LESUNG BATU DI SITUS PULAU PANGGUNG DAN PAJAR BULAN, KABUPATEN LAHAT, PROVINSI SUMATERA SELATAN - Azmi, Seffiani Dwi; Indriastusti, Kristantina (Siddhayatra, 2018)
Increasing food needs equire people to create equipment that can help their daily lives by utilizing local wisdom. One of the tools created was stone mortar which serves as a container for pounding grains or rice. The number of stone mortar findings can indicate that more community needs must be met. This makes the manufacture of stone mortar which can be seen from the remains scattered in Pajar Bulan Subdistrict so that a typological study of the shapes and reliefs that develop there is needed. The method used is quantitative and qualitative methods with data sources from literature studies. The analysis used is a special analysis, namely through morphological and stylistic analysis to observe the physical characteristics of artifacts. The results obtained are there are 3 types of stone mortar, Oval Circuit (A1) mortar, rectangle with sharp angle (B1), Oval Easimove (A2) type.